The Neotropical species of the genus Eleusis Laporte, 1835 with description of the new genus Eleusima (Coleoptera: Staphylinidae: Osoriinae) - Irmler, Ulrich (Contributions to Entomology = Beiträge zur Entomologie, 2017)
According to Herman (2001) 24 species of the genus Eleusis were known from the Neotropical region before this study. Among these, the following 11 species are newly synonymised: E. cephalotes Bernhauer, 1904, and E. puncticeps Bernhauer, 1921 are synonyms to E. bicolor (Erichson, 1840); E. dubius (Sharp, 1876), Eleusis infima Sharp, 1887, E. marginicollis Bernhauer, 1921, E. armuellensis Bierig, 1931 are synonyms to E. nigerrima Fauvel, 1864; E. pallidipennis (Fauvel, 1864), E. corvina Sharp, 1887, E. flavipennis Sharp, 1887, and E. darlingtoni Blackwelder, 1943 are synonyms to E. interrupta (Erichson, 1840); E. mixta Sharp, 1887 is synonym to E. sctia Sharp, 1887. The new genus Eleusima is described with the new species E. platysoma spec. nov. The following new species of the genus Eleusis are described: E. genieri spec. nov., E. castanea spec. nov., E. rufipennis spec. nov., E. ecuadoriensis spec. nov., E. andina spec. nov., E. boliviana spec. nov., E. hondurana spec. nov., E. nigrita spec. nov., E. elongate spec. nov., E. panamaensis spec. nov., E. peruviana spec. nov., E. struyvei spec. nov., and E. tenuis (Fauvel, 1864), formerly synonymised with E. humilis, was found to be a distinct species and named here E. fauveli spec. nov., E. indica Kraatz, 1859, also synonymised with E. humilis (Erichson, 1840) is a distinct species as well, but not part of the Neotropical fauna. Overall, 24 Eleusis species are now known from the Neotropical region which can be separated into 3 species groups.Nomenclatural ActsEleusima – urn:lsid:zoobank.org:act:8E861E42-9378-477C-BD35-1B6D0697B867Eleusima platysoma spec. nov. – urn:lsid:zoobank.org:act:CCD6DF2B-5665-41ED-A2BA-55ED02C72A23Eleusis andina spec. nov. – urn:lsid:zoobank.org:act:23436043-BE8A-46AE-97E5-15BDAEECF02AEleusis boliviana spec. nov. – urn:lsid:zoobank.org:act:63DF628A-E08F-4D9E-9518-B5C00599B8D8Eleusis castanea spec. nov. – urn:lsid:zoobank.org:act:3121AA37-99A7-4839-9172-A2A98F9E5372Eleusis ecuadoriensis spec. nov. – urn:lsid:zoobank.org:act:774F9A2D-25FE-426C-8A32-C52AB801876BEleusis elongate spec. nov. – urn:lsid:zoobank.org:act:FD5048E3-6760-43B9-BB13-D5FC480530A1Eleusis fauveli spec. nov. – urn:lsid:zoobank.org:act:2C9C2952-39B3-4ECE-B7A9-CDE2E37B1E3EEleusis genieri spec. nov. – urn:lsid:zoobank.org:act:BAA0CF84-6884-461A-877A-44CA8B6B544AEleusis hondurana spec. nov. – urn:lsid:zoobank.org:act:BB492AC3-EF93-4F93-90E5-FD266A957102Eleusis nigrita spec. nov. – urn:lsid:zoobank.org:act:7786C482-50D4-419D-85FB-FB349801FD11Eleusis panamaensis spec. nov. – urn:lsid:zoobank.org:act:7078364E-083E-4BC7-ADE2-045789D19FFAEleusis peruviana spec. nov. – urn:lsid:zoobank.org:act:819FB601-081E-4EEF-BAD3-2363C6D299CFEleusis rufipennis spec. nov. – urn:lsid:zoobank.org:act:B6989833-5DD4-492E-969F-DD1F4E6E97E9Eleusis struyvei spec. nov. – urn:lsid:zoobank.org:act:0BB5EBEE-6C8F-49D9-9D90-7178E660227F